НОВЫЕ ВИДЫ АТРИПИД (БРАХИОПОДЫ) ИЗ ДЕВОНСКИХ ОТЛОЖЕНИЙ МОНГОЛИИ - Алексеева Р.Е.; Комаров В.Н. (My University, 2004)
Four new types of atripidia from emssky deposits in Mongolia are described: Antypa (Planatrypa) aenigmatosis, Antryparia (Antryparia) plenus, Spinatiypa (Spinatrypa) mirus and Salarina explicatus.
Keywords: 564.832:551.734.2(517.3)